Insights on the performance of sintered silt ash-blended cement: experiments and thermodynamic simulation - Li, Zhipeng; Liu, Zhengxiang; Zhang, Hongguang; Luo, Qiling; Long, Wu-Jian (Frontiers in Materials, 2023)
The dredged silt exposed to the air is highly expected to be used to replace cement in large quantities due to its richness in aluminosilicates, which is in line with the dual-carbon background. Herein, a systematic exploration on the basic properties and hydration products of sintered silt ash-blended (SSA-blended) cement is conducted, using experiments and thermodynamic simulations. The results show that in the process of adding SSA to 50%, the compressive property and chloride ion permeation resistance are enhanced first and then weakened, whereas the flexural property is weakened gradually. Among them, with the addition of 10% SSA, the compressive strength can reach 65.2 MPa and the electric flux is 37.3% lower than that of Portland cement (PC), and the chloride ion permeability is rated as the lowest. As SSA increases, the FTIR spectra show that the reduction rates of bound water, ettringite and Ca(OH)2 are accelerated gradually; SEM observation shows that the cement-based gelling skeleton has undergone a transition from dense to loose; the thermodynamic simulation results show that C-S-H increases first and then decreases, implying that SSA has a certain pozzolanic activity. In addition, the evolution laws of other hydration products are highly consistent with the analysis results of FTIR and SEM.